Mark Manders : 13 drawings. - Documenta, Kassel ([S.l.] : [s.n.], 2002)
Free paper with drawings, given away to visitors of Documenta 11
Mark Manders, Documenta 11, Kassel, [2002-06-08. 2002-09-15]
Engels
boek
Keywords: Manders, Mark